1988
DOI: 10.1113/jphysiol.1988.sp016934
|View full text |Cite
|
Sign up to set email alerts
|

Increased tubuloglomerular feed‐back mediated suppression of glomerular filtration during acute volume expansion in rats.

Abstract: SUMMARY1. Volume expansion is currently believed to change the intrinsic properties of the juxtaglomerular apparatus such that the sensitivity of the tubuloglomerular feedback (TGF) mechanism is reduced, thus allowing glomerular filtration rate, and hence salt and water excretion, to rise. Recent studies conflict with this view and indeed the older literature reveals that the rise in glomerular filtration rate (GFR) under these conditions is far more modest than would be expected if TGF control were eliminated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…As a consequence of this shift, GFR in the post-benzolamide phase was actually higher than in control. The hyperfiltration and the pattern of TGF resetting caused by benzolamide are strikingly similar to those seen previously during acute extracellular volume expansion, another state in which the macula densa is exposed for some time to an increase in NaCl concentration (13,17). Interestingly, the benzolamideinduced TGF resetting outlasted the actual duration of the high perfusion stimulus.…”
supporting
confidence: 62%
“…As a consequence of this shift, GFR in the post-benzolamide phase was actually higher than in control. The hyperfiltration and the pattern of TGF resetting caused by benzolamide are strikingly similar to those seen previously during acute extracellular volume expansion, another state in which the macula densa is exposed for some time to an increase in NaCl concentration (13,17). Interestingly, the benzolamideinduced TGF resetting outlasted the actual duration of the high perfusion stimulus.…”
supporting
confidence: 62%
“…Intravascular infusion of saline at 0.080 ml/min was used to provoke maximal physiologic diuresis in response to subacute fluid loading. 20 Infusion and data collection were continued until several voids had occurred, typically requiring 5-6 hr. Bladder pressure data was not collected as no intravesical catheters were placed in this group.…”
Section: Free Voidingmentioning
confidence: 99%
“…These studies at least suggested that decreased sensitivity of TGF may contribute to the efficient off-loading or excretion of Na ϩ and water following SE. However, other studies concluded that TGF persisted after more modest SE, actually acting to limit the increase in GFR (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Several prior studies have examined TGF characteristics during acute volume loading, but with somewhat different techniques and goals in mind (4,5,7,8,18,22,39). For the most part, the earlier studies utilized open-loop techniques by perfusing the macula densa segments from the late proximal tubule and assessing SNGFR or stop-flow pressure responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation